Implementasi Kegiatan Ecoprint untuk Mengembangkan Kreativitas dan Karakter Peduli Lingkungan pada Siswa di SD Negeri 1 Waringinkurung - Asih Setyo Rini; Siti Nurelisah; Tasya Naila Hayati; Annisa Nurul Ulya (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Environmental awareness needs to be instilled from an early age because children are the next generation who will face various ecological challenges in the future. One approach that can be implemented is ecoprint training, a technique for printing motifs on fabric using natural leaves, flowers, and plants without using harmful chemicals. This study aims to describe the implementation of ecoprint activities in developing creativity and environmentally conscious character in students at SD Negeri 1 Waringinkurung. The study used a descriptive qualitative approach with subjects in grades IV and V, teachers, and the principal. Data were collected through observation, interviews, documentation, and student work, then analyzed using the Miles and Huberman model. The results showed that ecoprint activities were able to enhance students' creativity through exploration of shapes, colors, and compositions of natural motifs, while simultaneously fostering environmentally conscious character through the use of natural materials, maintaining cleanliness, reducing waste, and preserving plants. Thus, ecoprint is a fun, contextual, and effective learning alternative to support character education in elementary schools.